2016
DOI: 10.1007/s11661-016-3444-4
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Reactive Ni3Sn4 Formation and Growth in Ni-Sn Interlayer Systems

Abstract: The near-isothermal growth and formation of Ni 3 Sn 4 intermetallic compounds (IMC) in Ni-Sn interlayer systems was studied in the solid state at 473 K (200°C) and under solid-liquid conditions at 523 and 573 K (250°C and 300°C) from an initial state of a few seconds. Scalloped solid-state IMC formation was mainly driven by grain boundary diffusion of Ni through the IMC layer combined with the grain coarsening of the IMC layer. Under solid-liquid conditions, the formation of faceted and needle-shaped Ni 3 Sn 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…Both Sn preforms [26] and deposited layers have been used. The deposited layers have been electroplated [27,28,30], e-beam [32], thermally evaporated, sputtered [25,32] or a combination of the abovementioned methods. …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Both Sn preforms [26] and deposited layers have been used. The deposited layers have been electroplated [27,28,30], e-beam [32], thermally evaporated, sputtered [25,32] or a combination of the abovementioned methods. …”
Section: Resultsmentioning
confidence: 99%
“…The high-temperature compatibility is the most frequent reason for investigating the Ni-Sn system [25][26][27]. In addition, Nickel and tin are relatively low-cost materials which make them attractive for more cost-sensitive applications [26,28]. The formed IMCs may also have matching thermomechanical material properties which may be critical in applications with very high operation temperatures [29].…”
Section: Rationale For Ni-snmentioning
confidence: 99%
See 1 more Smart Citation
“…It is known that a dense Ni 3 Sn 4 IMCs layer always forms at a Sn/Ni interface [22]. Previous studies demonstrated that the Ni 3 Sn 4 IMC layer was an excellent elemental diffusion barrier layer, which could inhibit the mutual diffusion of Ni and Sn [22,23]. The Ni 3 Sn 4 phase is few found in the joint soldered with Ni/Sn composite solder (Fig.…”
Section: Metallurgic Reaction Mechanism Of Cu Jointsmentioning
confidence: 97%
“…Therefore, to improve the reliability of solder joints, a Ni barrier is typically introduced between the Cu and Sn solder to reduce the IMC thickness. Studies have shown that the growth kinetics of IMC layers at the interface between Ni and liquid Sn-based solder is much lower than those at the Cu/solder interface (Lis et al , 2016; Faizan, 2015; Akihiro et al , 2016). Currently, a Ni/Sn-based solder/Ni interconnected structure is widely used in electronic packaging.…”
Section: Introductionmentioning
confidence: 99%